Enactive interventions can enhance agency, health, and social relationships during childhood - Lozada, Mariana (2024)
In this article we aim to demonstrate how enactive interventions can foster a healthy interplay between mind, body, and social environments, evidenced at multiple levels and assessed from first-, second- and third-person perspectives. As proposed by Varela and Shear (1999) in the field of neurophenomenology, third-person perspectives (e.g., cortisol measurements) can be enriched with inquiries about subjective experience (Depraz et al., 2003). Consistent with this, qualitative methodologies used in the described studies allowed in-depth exploration of the complex transformations experienced by participants. It is worthy of note that in addition to chronic stress reduction, children made use of the novel practices, indicating that agency had been developed in this aspect and enabling them to play a more active role in coping with potential challenges. A similar trend was observed in the social domain since children became more agentive in their interactions with others. This agency enhancement in the social dimension may also have played a significant role in promoting children´s wellbeing, given the fundamental involvement of affection and socialization in health processes (e.g., Haas et al., 2010; Trevarthen et al., 2018; Carozza and Leong, 2021; Kornienko et al., 2022). In accordance with this, as warmth and acceptance were central to the intervention, it is likely that self-other awareness activities and non-competitive play favored a nurturing atmosphere within the group, promoting participatory sense-making processes.In sum, in this article we aimed to share our experience with enactive interventions that can enhance children´s health and wellbeing through agentive transformative processes. We believe that this kind of embodied experience can serve them well in their daily lives and can be incorporated easily into educational contexts, promoting children´s healthy development.